The impact of aging on the properties of heat-treated iroko wood used as a terrace deck for 10 years - Ermeydan, Mahmut A.; Tomak, Eylem D. (Taylor & Francis Inc, 2025)
The exposure period and environmental factors can significantly influence the surface degradation of wood. Extended exposure periods are needed for accurately assessing a material's long-term performance, making it essential to study how prolonged exposure affects wood properties. This research focused on examining the impact of heat treatment on the physical properties (dimensional stability, water uptake, and contact angle), mechanical properties (flexural and compression), and surface analysis (FTIR, SEM, roughness, and color) of iroko wood used as a terrace deck over a 10-year period in Bursa, T & uuml;rkiye. Findings revealed that the surface roughness and water uptake of aged iroko increased considerably after exposure. Although heat treatment improved surface quality (roughness, wettability) and color stability initially, heat-treated (HT) iroko partially lost those improvements after the 10-year exposure period. The compression strength and modulus of elasticity of aged HT iroko slightly decreased compared to unaged HT samples, where the rupture modulus decreased remarkably. FTIR analysis and SEM images indicated notable changes in surface composition in heat-treated wood after exposure.
Keywords: Aging; iroko; surface changes; dimensional stability; mechanical properties